Sosialisasi Pendaftaran Nomor Pokok Wajib Pajak (NPWP) pada Usaha Kecil dan Menengah di Kecamatan Rajabasah Bandar Lampung: Pengabdian - Waspodo, Lego; Wiryawan, Driya; Kholillulloh, Fajar; Primasari, Dona; Widianingsih, Rini; Ulin Nuha, Achmad (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The community service team had an idea to increase public awareness of paying taxes by holding a socialization of NPWP registration to the community in the Rajabasah sub-district. The community service was carried out in two sessions, namely: the first session, the community service team to improve participants' understanding of the socialization of NPWP registration was carried out using the lecture method. The lecture method is considered effective in improving participants' knowledge of socialization. The second session, a Focus Group Discussion (FGD), involved training participants in small groups accompanied by community service team members. The FGD method is expected to improve participants' understanding of the socialization of the requirements, processes, and steps taken during NPWP registration. Data was taken in two stages. The first stage of the questionnaire was distributed at the beginning of the socialization, and the second stage of data collection was completed at the end of the meeting. The analysis results showed increased participants' understanding of the requirements, processes, and steps needed during NPWP registration.